2015
DOI: 10.1148/radiol.14140284
|View full text |Cite
|
Sign up to set email alerts
|

CT Features of Early Type II Endoleaks after Endovascular Repair of Abdominal Aortic Aneurysms Help Predict Aneurysm Sac Enlargement

Abstract: The strongest indicators for aneurysm sac enlargement are complex IMA-LA type II endoleak and the diameter of the largest feeding and/or draining artery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 21 publications
2
29
2
Order By: Relevance
“…However, the difference between two groups was not statistically significant. This result is not directly comparable to that reported by Muller-Wille R, et al 8 because they used a different method of outcome measurement. Muller-Wille R, et al 8 classified simple and complex type II endoleak into four subtypes, and they found complex IMA-LA subtype to be significantly associated with aneurysmal sac enlargement (OR: 20.8, 95% CI: 4.9-88.9; p<0.001).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…However, the difference between two groups was not statistically significant. This result is not directly comparable to that reported by Muller-Wille R, et al 8 because they used a different method of outcome measurement. Muller-Wille R, et al 8 classified simple and complex type II endoleak into four subtypes, and they found complex IMA-LA subtype to be significantly associated with aneurysmal sac enlargement (OR: 20.8, 95% CI: 4.9-88.9; p<0.001).…”
Section: Discussioncontrasting
confidence: 99%
“…This result is not directly comparable to that reported by Muller-Wille R, et al 8 because they used a different method of outcome measurement. Muller-Wille R, et al 8 classified simple and complex type II endoleak into four subtypes, and they found complex IMA-LA subtype to be significantly associated with aneurysmal sac enlargement (OR: 20.8, 95% CI: 4.9-88.9; p<0.001). Number of feeder arteries showed a significantly greater proportion of 2 or less arterial feeders in the transient group (91.7%) than in the persistent group (52.6%); p = 0.012.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The clinical importance and need for intervention in early type II endoleaks is somewhat controversial, as nearly half of these will resolve spontaneously within 6 months, whereas some will become persistent and may result in further enlargement of the aneurysm (4À6). In a retrospective study performed by Muller-Wille et al, the authors concluded that the strongest predictor for aneurysm sac enlargement in type II endoleaks was the presence of complex inferior mesenteric artery or lumbar artery endoleaks, defined as multiple inflow and/or outflow vessels (7).…”
mentioning
confidence: 99%